ANWAR PRISON TO PALACE PM FOR ALL : Malaysians speak Up for Reformasi and Unity to Succeed - Krishnamoorthy Muthaly (Krishnamoorthy Muthaly, 2023)
"PRISON TO PALACE, PM FOR ALL" is the story of Anwar Ibrahim's turbulent, moving, bold, and visionary journey from a village boy to the Prime Minister of Malaysia. The chapters weave through the intricacies of political challenges, repression, injustice, and trials and tribulations. Eventually, Anwar achieved his childhood dream of becoming Malaysia's leader. The book traces his rise to power, fall from grace, and his resilience in the face of adversity, including ten years of inhumane treatment in prison. Despite the odds, Anwar turned his adversity into an opportunity for growth, and his experience in solitary confinement led to brilliant, innovative, and decisive thinking. He reflected positively on life and has returned to reset and refresh Malaysia towards reform, unity, peace, and harmony. The book details Malaysia's changing political history and showcases penetrating insights into the events leading to Anwar's crowning glory. It portrays stories of hurt and healing, abuse and forgiveness, gloom and glory, and tears and triumph.